Amphibian fauna of Pakistan with notes on future prospects of research and conservation - Muhammad Rais; Waseem Ahmed; Anum Sajjad; Ayesha Akram; Muhammad Saeed; Hannan Nasib Hamid; Aamina Abid (ZooKeys, 2021)
Research on amphibians and their conservation have gained worldwide attention, as the group includes the highest number of threatened and Data Deficient species when compared to other vertebrates. However, amphibians have long been neglected in wildlife conservation, management decisions, policy making, and research agendas in Pakistan. In this paper, an annotated checklist of the 21 amphibian species of Pakistan, a key to their identification, and detailed discussions on variation in species, including the genera Minervarya and Sphaerotheca, are provided. We found a statistically significant difference in the morphometric measurements of males but non-significant difference in the females of the two forms (rusty dorsum and dotted dorsum) of S. maskeyi. Some genera, such as Microhyla, Uperodon, Minervarya, Allopaa, Chrysopaa, Euphlyctis, Nanorana, and Sphaerotheca, in Pakistan are in need of additional data for molecular and morphological comparisons with taxa in other South Asian countries. The predicaments of amphibian research in Pakistan are discussed, gaps identified, and suggestions are made. Although the occurrence of chytrid fungus in Pakistan is predicted of low likelihood, a lack of data merits studying the prevalence of the fungus, particularly in the northern regions of the country which exhibit complex and dynamic ecosystems. It is recommended that systematic and coordinated surveys are conducted throughout the country to build a database of species occurrences and distributions. Additionally, the monitoring of wild populations and threat mitigation, as well as appropriate legislation, are suggested as long-term measures. By adopting an inclusive wildlife conservation approach in Pakistan, amphibians could be integrated into wildlife conservation and management efforts.